The exit of mouse embryonic fibroblasts from the cell-cycle changes the nature of solvent exposure of the 5'-methylcytosine epitope within chromatin. - Selcen Çelik; Yan Li; Chris O'Neill (PLoS ONE)
The methylation of CpG dinucleotides is a pervasive epigenetic signature with critical roles governing genomic stability and lineage-specific patterns of gene expression. Reprogramming the patterns of CpG methylation accompanies key developmental transitions and the onset of some pathologies, such as cancer. In this study we show that levels of immuno-detectable 5meC decreased as mouse embryonic fibroblasts withdraw from the cell-cycle (became mitotically quiescent), but increased as they aged in culture. Two pools of 5meC epitope were found to exist, one solvent exposed after acid-induced denaturation of chromatin and another that required the additional step of tryptic digestion for detection. Proliferative cells displayed a relatively greater accumulation of detectable 5meC within the trypsin-sensitive pool than did quiescent cells. A substantial proportion of the 5meC was associated with a large number of heterochromatic foci scattered throughout nuclei, yet much of this was masked in a trypsin-sensitive manner, particularly in young proliferative cells. This study showed that the growth status of cells changed the level of solvent exposure of 5meC in fibroblasts and the long-accepted conventional methods of immunolocalization underestimate the level of 5meC in cells. This resulted in an artefactual assessment of the levels and patterns of nuclear localization of the antigen. The use of an additional tryptic digestion step improved antigen retrieval and revealed a more dynamic response of 5meC levels and distribution patterns to changes in the cell's growth state. This discovery will provide a basis for investigating the role of changes in chromatin structure that underlie this dynamism.